Long noncoding RNA AC003092.1 promotes temozolomide chemosensitivity through miR-195/TFPI-2 signaling modulation in glioblastoma. Issue 12 (December 2018) - Xu, Ningbo; Liu, Boyang; Lian, Changlin; Doycheva, Desislava; Fu, Zhao; Liu, Yanting; Zhou, Jian; He, Zhenyan; Yang, Zhao; Huang, Qiongzhen; Zeng, Huijun; Guo, Hongbo
Abstract Temozolomide (TMZ) and radiation therapy combination for glioblastoma (GB) patients has been considered as the most effective therapy after surgical procedure. However, the overall clinical prognosis remains unsatisfactory due to intrinsic or developing resistance to TMZ. Recently, increasing evidence suggested that long noncoding RNAs (lncRNAs) play a critical role in various biological processes of tumors, and have been implicated in resistance to various drugs. However, the role of lncRNAs in TMZ resistance is poorly understood. Here, we found that the expression of lncRNA AC003092.1 was markedly decreased in TMZ resistance (TR) of GB cells (U87TR and U251TR) compared with their parental cells (U87 and U251). In patients with glioma, low levels of lncRNA AC003092.1 were correlated with increased TMZ resistance, higher risk of relapse, and poor prognosis. Overexpression of lncRNA AC003092.1 enhances TMZ sensitivity, facilitates cell apoptosis, and inhibits cell proliferation in TMZ-resistant GB cells. In addition, we identified that lncRNA AC003092.1 regulates TMZ chemosensitivity through TFPI-2-mediated cell apoptosis in vitro and in vivo. Mechanistically, further investigation revealed that lncRNA AC003092.1 regulates TFPI-2 expression through miR-195 in GB. Taken together, these data suggest that lncRNA AC003092.1 could inhibit the function of miR-195 by acting as an endogenous CeRNA, leading to increased expression of TFPI-2; this promotes TMZ-induced apoptosis, thereby making GB cells more sensitive to TMZ. Our findings indicate that overexpression of lncRNA AC003092.1 may be a potential therapy to overcome TMZ resistance in GB patients.